The Role of marketing mix (7P) Strategy Towards Customer Satisfaction - Kusdiana, Yayu; Yulita, Rahma (Lembaga Riset dan Inovasi Al-Matani, 2024)
KPPBC Type Madya Cukai Malang as part of the Directorate General of Customs and Excise is a government institution that has duties and authorities in the field of customs and excise. As a government bureaucracy engaged in the government service sector, the Malang Customs Office also applies the marketing mix (7P) to support service user satisfaction, the company's marketing system namely product, price, place, promotion, people, process and physical evidence. Service user satisfaction is one of the parameters that is continuously measured to improve public service performance in an effort to change the culture of service-oriented organisations. In addition, if there are still shortcomings, improvements can be made in a better direction. The research method used in writing this scientific work is a qualitative approach to thoroughly and comprehensively reveal all aspects related to the influence of the marketing mix on service user satisfaction at the Malang Customs Office. Data collection is done by conducting interviews and observations. The results of the study indicate that the product and promotion variables do not directly affect service user satisfaction, while the price, place, people, process and physical evidence variables affect service user satisfaction.